A neuro-fuzzy approach to grinding process control (2008)
Grinding is one of the most important finishing operations and it is very useful in our automobile industries. The paper presents a control system for grinding process using neuro-fuzzy technique. The maximum grinding temperature is very important since too high temperature will lead to surface burns and thermal damage to the grinding wheel as well as the workpiece material. Neuro-fuzzy model was used to analyze the grinding wheel performance index as it affects the general grinding operations of the grinding process. The research work can be applied to any other grinding process, whether it is a wet or dry grinding process. However, the work is new as it appears to be the first application of neuro-tuzzy grinding operations.